Panax notoginseng extract and total saponin suppress diet-induced obesity and endoplasmic reticulum stress in epididymal white adipose tissue in mice - Yi Tan; Xutao Zhang; Yan Zhou; Lingchao Miao; Baojun Xu; Haroon Khan; Yitao Wang; Hua Yu; Wai San Cheang (BMC, 2022)
Abstract Background Investigation on protective effects of Panax notoginseng against obesity and its related mechanisms is incomplete. Present study aimed to investigate the potential anti-obesity effect of the total saponins (PNS) and ethanolic extract of P. notoginseng (PNE). Methods Six-week-old male C57BL/6J mice received 45% kcal fat diet for 12 weeks to induce obesity. Oral administration of PNS and PNE at 20 mg/kg/day was applied for the last 4 weeks in the obese mice. Lipid profile was determined by ELISA. Histological examination was performed in liver and fat tissues. Protein levels were measured by Western blot. Results PNS and PNE did not cause weight loss. PNE but not PNS decreased the mass of epididymal and retroperitoneal white adipose tissue, accompanied by a reduction in adipocyte hypertrophy. PNS and PNE improved lipid profile by reducing the concentrations of triglyceride, total cholesterol and low-density lipoprotein cholesterol in plasma or liver samples. PNS and PNE also relieved fatty liver in obese mice. PNS and PNE inhibited expression and phosphorylation of endoplasmic reticulum (ER) stress-responsive proteins in hypertrophic adipose tissue. Conclusions PNS and PNE can regulate ER stress-mediated apoptosis and inflammation to alleviate obesity.